2006
DOI: 10.1116/1.2359735
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of spatially programmable chemical vapor deposition: Model-based uniformity∕nonuniformity control

Abstract: Articles you may be interested inDevelopment of a spatially controllable chemical vapor deposition reactor with combinatorial processing capabilities Rev. Sci. Instrum. 76, 062217 (2005); 10.1063/1.1906183 Effect of NH 3 thermal treatment on an atomic layer deposited on tungsten films and formation of W-B-N A new chemical vapor deposition ͑CVD͒ reactor design was developed to intentionally induce spatially nonuniform film thickness deposition patterns on a single wafer. A segmented showerhead design allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Utilizing modified equipment, including a turntable substrate holder and a slide with masks, a combinatorial library of VDP films with varying thickness, compositions and orientations was produced within a single deposition run from the monomers 3,3′,4,4′‐biphenyldianhydride (BPDA) and 4,4′‐diamino‐ p ‐ terphenyl 311. Similar combinatorial reactor designs can prove effective in honing in to the right deposition conditions for other CVD polymerization methods without an exhaustive design of experiments 321, 322…”
Section: Unifying Themesmentioning
confidence: 99%
“…Utilizing modified equipment, including a turntable substrate holder and a slide with masks, a combinatorial library of VDP films with varying thickness, compositions and orientations was produced within a single deposition run from the monomers 3,3′,4,4′‐biphenyldianhydride (BPDA) and 4,4′‐diamino‐ p ‐ terphenyl 311. Similar combinatorial reactor designs can prove effective in honing in to the right deposition conditions for other CVD polymerization methods without an exhaustive design of experiments 321, 322…”
Section: Unifying Themesmentioning
confidence: 99%
“…The result showed that the profile regulation was finer, and the process quality was continually promoted with the rising of the polynomial order. Adomaitis and coworkers [12][13][14][15] proposed and designed a spatially programmable chemical vapor deposition prototype. This novel solution divided the gas inlet structure into many mass-flow-rate independently controllable sub-regions and then detected the species concentration profile above the wafer by an in situ mass spectrometer to drive the feedback control, which reprogrammed the mass flow rate of each gas inlet to finely regulate the spatial distribution of mass transport.…”
Section: Introductionmentioning
confidence: 99%
“…In the second example we consider data produced by the Programmable CVD reactor system [5,6,9,10], a reactor designed to test spatially controlled CVD concepts. The main feature of this system is its segmented showerhead design that allows independent control of feed gas composition to each segment.…”
Section: Model Comparison For the Spatially Programable Cvd Reactormentioning
confidence: 99%
“…In Taylor and Semancik [12], microhotplate devices were used to control the temperature in an array of micro-scale substrate samples; it was found that temperature gradients in the microhotplate supports resulted in a microstructurally graded film on the support legs. Finally, the Programmable Reactor system [5,6,9,10] features a segmented shower head design where each segment is fed individually with reactant gases and exhaust gas is pumped back up through each segment. This concept was tested in a three-zone prototype tungsten deposition system to evaluate the system's ability to manipulate gas phase composition across the wafer surface [5,6] and to demonstrate its true programmable nature using a modelbased approach to controlling spatial deposition patterns across the wafer surface [9,10].…”
Section: Combinatorial Cvdmentioning
confidence: 99%
See 1 more Smart Citation